Technical review on crumb rubber drying process and the potential of advanced drying technique - Tham, Thing Chai; Hii, Ching Lik; Ong, Sze Pheng; Chin, Nyuk Ling; Abdullah, Luqman Chuah; Law, Chung Lim (Elsevier, 2014)
Intensive thermal energy and extensive drying period are required in rubber drying process due to its low conductivity and dielectric properties. Thus, selection of advanced drying techniques of crumbs rubber is essential for the sake of efficiency and energy conservation. The integration of advanced dryers ranging from electromagnetic heater, fluidized bed dryer, heat pump and the vacuum environment were discussed in details in paper. In summary, cost and energy efficient dryer is the aim of this research work and it is important that this technology offers a robust and reliable solution to the rubber processing industry.